2018
DOI: 10.1016/j.eurpolymj.2018.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Redefining polyamide property profiles via renewable long-chain aliphatic segments: Towards impact resistance and low water absorption

Abstract: A series of renewable, long-chain, fatty acid-derived polyamides (PA) ranging from PA 6,14 to PA 6,18 were synthesized via polycondensation, yielding very high molecular weights and a remarkable property profile distinct from short-chain commercial grades. Most notably, synthesized polyamides exhibited good impact resistance, excellent stiffness-to-toughness balance and very low water absorption yet high oxygen and water vapour permeability; with this property profile being exemplified by PA 6,18. The increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
(58 reference statements)
3
31
0
Order By: Relevance
“…The NH bond density of the PA chain reduced with an augment in alkylene chain lengths, consequently in a debilitate of intermolecular H‐bonding; therefore, T m and T c values of bio‐based PAs decreased with an increase in the length of alkylene carbon chains (Figure 6c,d). These results were in full agreement with the findings reported by Nguyen et al 39 and Kolb et al 47 All integrated bio‐based PAs showed clear T m and T c peaks screening their semicrystalline like structure. Like the DAA monomer, this behavior was believed to be triggered by the H‐bonding interaction created chiefly amid the DAA monomers.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The NH bond density of the PA chain reduced with an augment in alkylene chain lengths, consequently in a debilitate of intermolecular H‐bonding; therefore, T m and T c values of bio‐based PAs decreased with an increase in the length of alkylene carbon chains (Figure 6c,d). These results were in full agreement with the findings reported by Nguyen et al 39 and Kolb et al 47 All integrated bio‐based PAs showed clear T m and T c peaks screening their semicrystalline like structure. Like the DAA monomer, this behavior was believed to be triggered by the H‐bonding interaction created chiefly amid the DAA monomers.…”
Section: Resultssupporting
confidence: 92%
“…So their IV is also increased with the increase of DAA chain length. This points out the correlation between polymerization reaction time and the degree of polymerization 25,39 …”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Figure 9a displays the percentage of water uptake of PA36,IA and PA36,36 after being submerged in water for 24 h compared with other PAs reported in previous literature [51]. PA36,IA displays a water absorption value of 0.2%, and PA36,36 displays water absorption of zero percent after 24 h of water submersion, representing hydrophobicity.…”
Section: Water Uptake Studymentioning
confidence: 89%
“…The T g of PA is associated with the monomers' chain length and the amide group concentration in the polymer chains. Therefore, longer monomer chains result in greater mobility of PA36,36, meaning it is much softer [50], so the synthesized bio-based PAs possess much lower T g values than the traditional rigid PAs, i.e., PA11 (T g = 68 • C), PA6,6 (T g = 80 • C), and PA6 (T g = 78 • C) [51]. Due to the existence of a rigid pyrrolidone ring in PA36,IA, it exhibits a higher storage modulus value than PA36,36.…”
Section: Thermal Propertiesmentioning
confidence: 99%